Success to Decay: Design and Economy from Self-Management to Free Enterprise Model. - Kostešić, Iva; Vukić, Fedja (Design Issues)
The article discusses design as a strategic tool used for the economic development of the Socialist Federal Republic of Yugoslavia. Topics discussed include the fusion of design and industry never having taken hold in its full capacity in Socialist Federal Republic of Yugoslavia (SFRY) for the long term, and the examination of factors including self-management, the design concept in Croatia and Slovenia, and the 1965 economic reform helping to understand the process of economic transformation in relation to design.